HEMORRHAGIC VASCULITIS (HENOCH-SCHONLEIN PURPURA) IN PREGNANCY: LITERATURE REVIEW AND CASE REPORT - Leonid Markin; Olena Rachkevych (Acta Medica Leopoliensia, 2021)
Aim. The paper aims at reviewing publications and analyzing a clinical case of Henoch-Schonlein purpura in a pregnant patient. This pathology is extremely rare in pregnancy (solely about 20 cases reported in the available literature)